Are Hamsters a Suitable Model for Evaluating the Immunogenicity of RBD-Based Anti-COVID-19 Subunit Vaccines? - Merkuleva, Iuliia A.; Shcherbakov, Dmitry N.; Borgoyakova, Mariya B.; Isaeva, Anastasiya A.; Nesmeyanova, Valentina S.; Volkova, Natalia V.; Aripov, Vazirbek S.; Shanshin, Daniil V.; Karpenko, Larisa I.; Belenkaya, Svetlana V.; Kazachinskaia, Elena I.; Volosnikova, Ekaterina A.; et al. (Viruses, 2022)
Currently, SARS-CoV-2 spike receptor-binding-domain (RBD)-based vaccines are considered one of the most effective weapons against COVID-19. During the first step of assessing vaccine immunogenicity, a mouse model is often used. In this paper, we tested the use of five experimental animals (mice, hamsters, rabbits, ferrets, and chickens) for RBD immunogenicity assessments. The humoral immune response was evaluated by ELISA and virus-neutralization assays. The data obtained show hamsters to be the least suitable candidates for RBD immunogenicity testing and, hence, assessing the protective efficacy of RBD-based vaccines.